Toxicity of Copper (Cu) on Abnormalities and Mortality of Tilapia Fish (Oreochromis niloticus L.) Prolarvae - Harlis, Wa Ode; Saputri, Desti Yulia; Malik, Nurhayu; Septiana, Andi; Resman, Resman (Jurnal Ilmiah Sains, 2026)
Contamination of the heavy metal Copper (Cu) in waters can inhibit fish growth by reducing the level of gonad maturity and closing the gill membranes. changes in activity, morphological abnormalities of the prolarvae and even death. This study aims to assess the toxicity of Copper (Cu) to tilapia fish prolarvae (Oreochromis niloticus L.). This research is a type of experimental research structured based on a Completely Randomized Design (CRD) pattern.  A total of 240 three-day-old tilapia prolarvae were divided into four treatment containers, namely Control, P1(2.0 mg/L), P2(2.5 mg/L), P3(3.0 mg/L), and each treatment consisted of three replications. Six hours after administration of copper, mortality parameters were observed, while prolarval abnormalities were observed after 48 hours.  Data were analyzed using one way ANOVA (Analysis of Varience) α=0.05. The results of the study showed that the average percentage of mortality for controls was (0%), P1(6.67%), P2(23.33%), P3(36.67%) while the forms of abnormalities found were kyphosis, lordosis, scoliosis and tail sticking. The research results show that copper (Cu) has a toxic effect because it increases the percentage of mortality and causes abnormalities in tilapia prolarvae (Oreochromis niloticus L.). Keywords: Copper (Cu); Oreochromis niloticus; prolarvae; toxicity